Dominance and subordination interactions among nestmates in pre and post-emergence phases of the basal eusocial wasp mischocyttarus (monogynoecus) montei (Hymenoptera, Vespidae) - Oliveira, V. C. [UNESP]; Desuó, I. C. [UNESP]; Murakami, Asn [UNESP]; Shima, S. N. [UNESP] (My University, 2012)
In basal eusocial wasps the social organization is based on a dominance hierarchy which is maintained through agonistic interactions. The dominant wasp is usually the most aggressive individual and assumes the reproductive function of the colony. These wasps lack morphological caste differences and the physiological conditions and behavioral repertoire define the role of each female in the nest. However, the position in the rank and its function in the colony are not definitive and tradeoffs in the social rank, at least in some species, are common. In this study 8 colonies of Mischocyttarus (M.) montei in pre and post-emergence phases of colonial development were observed in field conditions in order to study the interactions ofdominance and subordination among nestmates, thus allowing a better understanding of the establishment of the dominance hierarchy and consequently the social regulation of this species. Our results showed that all colonies in pre-emergence were founded by an association of females which had established the hierarchy previously in their natal nest. Such pattern may contribute to the success of association during pre-emergence, once it tends to reduce conflicts among cohorts during initial phases of colonial development, increasing the chances of colonial success. Duringpost-emergence, the conflicts tend to be more intense, usually involving more physical contacts and in this phase, tradeoffs in the social rank are more frequent. During post-emergence, the number of females increases, more cells are available to lay eggs and the reproductive condition of the main egg-layer is probably reduced, aggravating the competition for reproductive dominance of the colony.
Keywords: Dominance hierarchy; Eussocial wasps; Mischocyttarus; Polistinae